Influence of Silver Nanoparticles on the Growth of Ascitic and Solid Ehrlich Adenocarcinoma: Focus on Copper Metabolism - Daria N. Magazenkova; Ekaterina A. Skomorokhova; Mohammad Al Farroukh; Maria S. Zharkova; Zena M. Jassem; Valeria E. Rekina; Olga V. Shamova; Ludmila V. Puchkova; Ekaterina Y. Ilyechova (MDPI AG, 2023)
The link between copper metabolism and tumor progression motivated us to use copper chelators for suppression of tumor growth. We assume that silver nanoparticles (AgNPs) can be used for lowering bioavailable copper. Our assumption is based on the ability of Ag(I) ions released by AgNPs in biological media and interfere with Cu(I) transport. Intervention of Ag(I) into copper metabolism leads to the replacement of copper by silver in ceruloplasmin and the decrease in bioavailable copper in the bloodstream. To check this assumption, mice with ascitic or solid Ehrlich adenocarcinoma (EAC) were treated with AgNPs using different protocols. Copper status indexes (copper concentration, ceruloplasmin protein level, and oxidase activity) were monitored to assess copper metabolism. The expression of copper-related genes was determined by real-time PCR in the liver and tumors, and copper and silver levels were measured by FAAS. Intraperitoneal AgNPs treatment beginning on the day of tumor inoculation enhanced mice survival, reduced the proliferation of ascitic EAC cells, and suppressed the activity of HIF1α, TNF-α and VEGFa genes. Topical treatment by the AgNPs, which was started together with the implantation of EAC cells in the thigh, also enhanced mice survival, decreased tumor growth, and repressed genes responsible for neovascularization. The advantages of silver-induced copper deficiency over copper chelators are discussed.